The structure of pedicle and hard antler bone in the European roe deer (Capreolus capreolus): a light microscope and backscattered electron imaging study - Kierdorf, Uwe (Blackwell Science Inc, 2013)
Deer antlers are deciduous bony structures that develop from permanent frontal outgrowths, the pedicles. While growth and bone architecture of antlers have been studied in greater detail, information on pedicle formation and structure is scarce. The present study provides information on the structure of pedicle and hard antler bone in the European roe deer. A pronounced seasonal variation in pedicle architecture was observed, with high porosity around antler casting and a very compact bone structure during the hard antler stage. These observations suggest a corresponding marked variation also in the biomechanical properties of the pedicles. The seasonally alternating extensive resorption and formation processes make the pedicles of older deer heavily remodeled structures. Pedicles increase in thickness by apposition of primary bone that subsequently becomes replaced by secondary osteons. The antler cortex of roe deer is largely composed of a tubular framework of woven bone trabeculae with some remnants of mineralized cartilage, and primary osteons that have filled in the intertrabecular spaces. Secondary osteons are scarce, denoting little remodeling in antlers, which can be related to their short lifespan. The occurrence of cement lines around primary osteons indicates resorption on the trabecular scaffold prior to infilling of the intertrabecular spaces. The outer cortex showed a higher autofluorescence and a more immature structure than the main cortex, suggesting that it was secondarily formed by periosteal activity. Pedicles and antlers constitute a functional entity, and future histological and/or biomechanical studies should therefore consider both components of the cranial appendages.